Hate Speech in Media Discourse - Drożdż, Michał (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2017)
This article is an attempt to seek answers to the question of whether so-called hate speech in the media constitutes a reporting of facts and reflects real social and cultural life or pursues other aims, for example: the persuasive and manipulative creation of a desired reality innate in the functioning of a commercial and persuasive media. The author attempts from the axiological perspective of the media, as well as from the semiological and linguistic perspectives, to answer the question of what the role of media language is in shaping and promoting real attitudes of hostility and hatred, and conversely, how cultural and media tendencies shape hate speech in the media. The author does not analyse the material aspect of language, but rather tries to look critically at certain trends shaping new forms of media language that bear negative values.